Proteome research : (Springer, 2000)
Proteomics, a branch of functional genomics, can be defined as the large-scale analysis of proteins. In all these large-scale analysis processes there are three phases: (1) separation of the molecules to be analyzed; (2) characterization of the separated molecules; and (3) managing, handling and analysis of the data. This book is centered on the first two phases of proteomics, i.e. separation by two-dimensional electrophoresis and microcharacterization of the separated proteins.